Modeling and Experimental Verification of Surface Roughness for Grinding Monocrystalline Silicon Lens. Issue 7 (4th April 2022) - Yang, Fanxuan; Sun, Yuli; Wang, Yaji; Mo, Honglei; Zhu, Limin; Yuan, Hang; Lu, Bo; Zhang, Guiguan; Zuo, Dunwen
Abstract: The purpose of this paper is to study the formation mechanism of aspheric surface roughness and reveal the influence of processing parameters on the surface roughness. Aiming at the normal grinding method of aspheric surface, taking into account the geometric and kinematic characteristics of the grinding process of aspherical components, the surface roughness model of aspherical parts grinding is established and verified based on the theory of grinding technology. The relative error between the calculated value of the developed grinding surface roughness model and the actual measured value is within 20%. The model and experiments show that when the grinding wheel speed is 6000 r min −1, the workpiece speed is 70 r min −1, and the grinding depth is 70 μm, the aspheric surface roughness increases from about Ra0.1 μm at the center of the workpiece to about Ra0.4 μm at the outer edge of the workpiece. Increasing the grinding wheel speed, reducing the grinding depth and the workpiece speed can significantly reduce the surface roughness and make the aspheric surface roughness distribution tend to be uniform. The theoretical model proposed in this paper provides theoretical guidance for the controllable and efficient machining of aspheric components. Abstract : The purpose of this paper is to study the formation mechanism of aspheric surface roughness and reveal the influence of processing parameters on the surface roughness. Aiming at the normal grinding method of aspheric surface, the surface roughness model of aspherical parts grinding is established and verified based on the theory of grinding technology.